A Computer Simulation of Radiation-Induced Structural Changes and Properties of Multiperiod ZrNₓ/MoNₓ System - Sobol, O. V.; Meylekhov, A. A.; Bochulia, T. V.; Stolbovoy, V. A.; Gorban, V. F.; Postelnyk, A. A.; Shevchenko, S. M.; Yanchev, A. V. (Sumy State University, 2017)
Influence of the period value Λ (at different negative potential Ub that supplied during deposition) on phase composition, structure, stress-strain state and hardness of multiperiod coatings ZrNₓ/MoNₓ is investigated by using complex methods of validation structural state at combined with microindentation. Formation in layers ZrNx and MoNx the phases with cubic lattice and preferred orientation of crystallites with axis [100] is established. Stress-strain state of compression with increasing Ub is amplified and reaches maximum value (– 6.7 GPa) at Λ = 20 nm and Ub – 110 V. Hardness of coating increases with decreasing Λ from 300 to 20 nm. Coatings that obtained with Λ = 20 nm and Ub – 110 V have the highest hardness 44 GPa. Relaxation of structural compressive stresses and decreasing hardness is happening at smaller Λ and larger Ub – 110 V (as a result of radiation-stimulated forming defect and mixing). Data of computer modeling of defectiveness at atomic level at bombardment of ions that accelerated in field Ub are used to explain the results.

Використовуючи комплекс методів атестації структурного стану в поєднанні з мікроіндентуванням досліджено вплив величини періоду Λ (при різному негативному потенціалі Ub, що подається при осадженні) на фазовий склад, структуру, напружено-деформований стан і твердість багатоперіодних покриттів ZrNₓ/MoNₓ. Встановлено формування в шарах ZrNx і MoNx фаз з кубічної решіткою і переважною орієнтацією кристалітів з віссю [100]. Напруженно-деформований стан стиснення зі збільшенням Ub посилюється, досягаючи максимального значення (– 6,7 ГПа) при Λ = 20 нм і Ub – 110 В. Твердість покриттів збільшується зі зменшенням Λ від 300 до 20 нм. Покриття, отриманні при Λ = 20 нм і Ub – 110 В мають найбільшу твердість 44 ГПа. При меншому Λ і великому Ub – 110 В (в результаті радіаційно-стимульованого дефектоутворення і перемішування) відбувається релаксація структурних напружень стиску та зменшення твердості. Для пояснення отриманих результатів використані дані комп'ютерного моделювання пошкоджуваності на атомному рівні при бомбардуванні прискореними в поле Ub іонами.
Комп'ютерне моделювання радіаційно-стимульованих структурних змін і властивості багатоперіодної системи ZrNₓ/MoNₓ
Keywords: coatings; period; potential of bias; phase composition; structure; stress-strain state; solid solution; computer simulation; hardness; твердість; напружено-деформований стан; хімічні реакції; іони; кристаліти